Microsurgical Treatment Strategy of Vertebral Artery Fusiform Aneurysm—From the Standpoint of Hemodynamic Integrity and Perforator Preservation - Tsunoda, Sho; Inoue, Tomohiro (Frontiers in Neurology, 2021)
During treatment of vertebral artery (VA) fusiform aneurysms, it is critical to preserve peripheral perforators and anterograde blood flow of the VA and to reduce hemodynamic load to the contralateral VA. Even in the era of endovascular treatment, there are still many benefits to using microsurgical treatments with appropriate clip application and preservation of the perforators around the aneurysm, in conjunction with various bypass techniques. The ideal microsurgical technique involves reconstructive clipping that obliterates the aneurysm but preserves anterograde blood flow of the VA, followed by isolation of the aneurysm and VA reconstruction. If these two methods are unavailable, proximal clipping of the aneurysm combined with flow-augmentation bypass to the distal branch can be considered as an alternative surgical management. We discuss the microsurgical treatment of unruptured VA fusiform aneurysms in our surgical cases on the basis of a review of the current literature.